Pelestarian Kawasan Bersejarah Samarinda Seberang dengan Pendekatan Historic Urban Landscape - Rahim, Dzulfajrie; Barliana, Mokhamad Syaom (Department of Architecture, Faculty of Science and Technology, Alauddin State Islamic University, 2025)
Samarinda Seberang is a historical area in East Kalimantan that has historical value and spirit of place, reflected in the existence of rumah adat Kampung Tenun, masjid Shirathal Mustaqiem, and langgar Al Washielah. Modernization poses challenges to the sustainability of cultural heritage that forms the identity of the Samarinda Seberang urban area. This research aims to formulate a preservation strategy based on the Historic Urban Landscape (HUL) approach through a multi-aspect analysis (history, basic physical conditions, demographics and economy, and socio-culture), analysis of challenges and opportunities, and formulation of a preservation vision and proposal. Data collection of area morphology and visual interpretation of architectural elements became the basis of this research. The research method used was descriptive qualitative, with field observation techniques, purposive sampling interviews, and literature studies from government archives and local history sources. The results show that the application of HUL is effective in understanding the relationship between urban morphology and social and cultural structures, as well as providing direction for preservation actions. Recommendations in the form of preservation, reconstruction, restoration, and adaptative-reuse strategies for langgar Al Washielah can be the first step for the preservation of the Samarinda Seberang and the basis for the proposed cultural heritage preservation policy in Samarinda.